Improved protocol for high frequency plant regeneration through somatic embryogenesis in Carica papaya. - Mohamad Bukhori, Mohamad Fhaizal (Research in Biotechnology, 2013)
An efficient invitro method has been established for the production of whole plantlets of Caricapapaya L. var. Eksotika,C. papaya (E) using immature zygotic embryo (IZE) as explantsexcised from fruit 90 to 100 days (d) post-anthesis. Proliferating calluscultures were obtained by placing IZE explants on half-strength Murashige andSkoog (MS) medium supplemented with Ã‚Â carbenicillinand 2,4-dichlorophenoxyacetic acid (2,4-D) either aloneor in combination. MS medium augmented with 10 mg/L 2,4-DÃ‚Â and 250 mg/L carbenicillin was found to be effectivein providing the highest frequency (77.5%) of embryogenic callus formation. Allof the somatic embryos (100%) germinated after 3 months where only 90.4%produced normal hypocotyls when continuously cultured in 0.2 mg/L 6-benzyl aminopurine(BAP) and naphthaleneacetic acid (NAA). Subsequently,complete plants were regenerated (97.3%) when plantlets formed well-developedshoots and rootsin solid MS medium augmented with 0.5 mg/L indole-3-butyric acid(IBA).Regenerated plantlets were successfully acclimatised and subsequentlytransferred to the field. Histo-anatomical studies on the different stages ofsomatic embryogenesis were carried out in order to understand the morphogenicevents and growth responses of regenerated plants. This is a complete protocolon regenerable embryogenic cell suspension cultures in C. papaya (E).